'Public sector reform' : the Barbados experience : case study - Best-Winfield, Gail (CARICAD [St. Michael]BB, 2006)
Provides background information on Barbados, the structure of government, the economy and domestic and international challenges. Focuses on public sector reform, the challenges therein and the way forward.